Deteksi Pergerakan dan Kedipan Mata, pada Pemilihan Menu Display menggunakan Centroid Analysis berdasarkan Metode Face Landmark - Sri Mayena; Fitri Utaminingrum (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Detection is a process of identifying objects or activities that are usually done by humans, in order to facilitate the process of introduction and initialization in initiating all activities. In this section, the detection of eyes movement and eyes blink, used to be able to identify that, a system can be run by only eyes orders only, without the need for direct interaction, requiring that both humans and computers be in touch, Using the face landmark method, ascertained the eye area to produce high accuracy, in the test resulted in an accuracy rate of 93,33% success, in detecting eye features using face landmark, based on distance The nearest 20 cm closest, the research also shows rapid computing results in one-time detection of eyes features and the direction of the eyes movement takes only 0.170 seconds within 20 cm and 0.380 within 40 cm, with the help of digital image processing, the feature of the eyes will be easily processed by the computer and do the menu selection, which is meant to be a menu of the options of activities that can be used as one of the needed or orders of the user, with only activations Using a blink of an eye for 3-10 seconds, and a menu of 70x70 pixels, will be activated, and can be utilized by the nurse in understanding the activity that the user wants to do, especially the stroke sufferer, who can still use the eyes features As input that can be used to access the system.